Comparison of oncological outcomes and complication rate between radical hysterectomy and concurrent chemoradiotherapy in stage IIICr cervical cancer without parametrial invasion - Hee Yeun Yoon; Jong Mi Kim; Yoon Young Jeong; Yoon Hee Lee; Min Ju Kim; Yoon Seok Choi; Jung Min Ryu; Gun Oh Chong (BMC Cancer)
Abstract Background This study aimed to compare oncological outcomes and complication rates between radical hysterectomy (RH) and concurrent chemoradiotherapy (CCRT) in patients with stage IIICr cervical cancer without parametrial invasion, based on differing treatment protocols at two institutions. Methods A total of 106 patients with biopsy-confirmed cervical cancer and lymph node metastasis detected on pretreatment imaging, but without evidence of parametrial invasion, were enrolled. Of these, 55 patients underwent RH, while 51 patients received CCRT. Oncological outcomes, complication rates, and recurrence patterns were analyzed and compared between the two groups. Results At a median follow-up of 62 months (range, 3–220 months), there were no statistically significant differences in disease-free survival or overall survival between the RH and CCRT groups (p = 0.7788 and p = 0.8757, respectively). However, the incidence of overall complications was significantly higher in the RH group compared to the CCRT group (54.5% vs. 19.6%, p < 0.0001). The RH group also demonstrated a significantly greater frequency of major complications (Clavien-Dindo grade III/IV: 23.6% vs. 3.9%, p < 0.0001). Patterns of recurrence differed between the groups: the RH group exhibited a higher rate of distant metastases (56.2% vs. 16.3%), whereas the CCRT group showed a higher incidence of local recurrence (64.3% vs. 25.0%, p = 0.026). Conclusion There were no significant differences in disease-free or overall survival between patients treated with RH and those treated with CCRT. However, RH was associated with a significantly higher rate of complications. Given these findings, CCRT may represent a more favorable treatment option for patients with stage IIICr cervical cancer without parametrial invasion.